2014
DOI: 10.1080/09168451.2014.932666
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of ALK5 inhibitor A-83-01 reduces burn wound contraction in rats by suppressing myofibroblast population

Abstract: Burn scar contracture that follows the healing of deep dermal burns causes severe deformation and functional impairment. However, its current therapeutic interventions are limited with unsatisfactory outcomes. When we treated deep second-degree burns in rat skin with activin-like kinase 5 (ALK5) inhibitor A-83-01, it reduced wound contraction and enhanced the area of re-epithelialization so that the overall time for wound closing was not altered. In addition, it reduced myofibroblast population in the dermis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…71 Recently, it has been demonstrated that activin-like kinase 5 (ALK5) inhibitor reduces burn wound contraction in rats by suppressing myofibroblast population. 72 Activin A and follistatin expression have also been investigated in different phases of scar evolution in humans. 73,74 Immunostaining of active phase of hypertrophic scars showed that activin A is expressed by myofibroblasts and dendritic cells.…”
Section: Activin a In Scar Formationmentioning
confidence: 99%
“…71 Recently, it has been demonstrated that activin-like kinase 5 (ALK5) inhibitor reduces burn wound contraction in rats by suppressing myofibroblast population. 72 Activin A and follistatin expression have also been investigated in different phases of scar evolution in humans. 73,74 Immunostaining of active phase of hypertrophic scars showed that activin A is expressed by myofibroblasts and dendritic cells.…”
Section: Activin a In Scar Formationmentioning
confidence: 99%